Coro Infanto-juvenil nos grupos corais do Projeto Guri (Regional Ribeirão Preto): repertório e formação do regente (educador musical) - Paziani, Juliana Damaris de Santana [UNESP] (2015)
The present work carried out our intention to perform the search of the repertoire studied by eighteen Children-Young choirs of the Guri Project (in the area of Ribeirao Preto city). The goal was to get to know their repertoires and examine them in order to observe their compositional characteristics, vocal range, languages and the kind of repertoire in its various genres and musical styles, analyzing their suitability to the age in which they were applied. The methodology adopted was a Content Analysis, in which we collected, categorized, described and analyzed the documents. The amount of collected data was about 431 items, which included musical scores, song lyrics and lyrics with harmony indications. According to the results of this study, we proposed a thought on the need of expanding such repertoire through the awakening of the singer senses, so that the students could be in contact with more musical diversity and, then, also expand their artistic experiences.